Distance Learning of Indonesian Early Childhood Education (PAUD) during the Covid-19 Pandemic - Heny Solekhah (International Journal of Emerging Issues in Early Childhood Education, 2020)
The outbreaks of Covid-19 influence the Indonesian education nationally, including early childhood education (PAUD). Since the school closures in March, the teachers have attempted to implement the distance learning. This study is conducted in a school in Kendal. The teacher shared her experiences in conducting the learning based on the emergency curriculum. It is found that the government has given the support by publishing the twelve books for the learning at home policy and providing the internet data. Most of the books are about playing with children and positive communication. Parents’ roles in distance learning have greater proportion than the teachers. Parents in this situation have the duties to supervise the learning, to conduct the learning, and to assist teachers in assessment. The teachers construct the weekly lesson plan, communicate the steps of learning process, and evaluate the students’ progress. However, both teachers and parents experience barriers due to the lack of skills in using technology and inability to provide learning materials to support six aspects of child development.